Behavioural consequences of nucleus accumbens dopaminergic stimulation and glutamatergic blocking in pigeons - Acerbo, Martín J. (2002)
Upon systemic administration of apomorphine, a potent dopamine agonist, pigeons show a bout of pecking behaviour. When the drug is repeatedly administered a sensitization takes place that is associated with pronounced discrimination learning. Here we show that intra-cerebral injections of apomorphine in the periphery of the nucleus accumbens of pigeons also elicit pecking. We additionally show that injections of 5-amino-phosphonohepatnoic acid, a NMDA-glutamate receptor blocker, into the Acc impairs the performance of a learned visual discrimination incorporating pecking as a choice response. We conclude that, as it is the case in mammals, the control mechanisms of learned sensory-motor behaviour in birds involves dopaminergic and glutamatergic synaptic transmission within the nucleus accumbens area.